2008
DOI: 10.1007/s00192-008-0572-4
|View full text |Cite
|
Sign up to set email alerts
|

A combined intravesical therapy with hyaluronic acid and chondroitin for refractory painful bladder syndrome/interstitial cystitis

Abstract: The aims of this study were to evaluate the efficacy and tolerability of intravesical instillations of high-molecular-weight hyaluronic acid (HA) 1.6% and chondroitin sulfate (CS) 2.0% in patients with refractory painful bladder syndrome/interstitial cystitis (PBS/IC) and to observe their impact on Quality of Life. Twenty-three women were enrolled. They received bladder instillations with HA and CS weekly for 20 weeks and then monthly for 3 months. Mean follow-up after completion of therapy was 5 months. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 26 publications
(31 reference statements)
4
45
2
Order By: Relevance
“…Steinhoff et al found a 45% response rate after initial 3 months with instillation of 40 ml CS 0.2%, and Nickel et al reported that instillation of CS 2% produced a 60% response rate at 6 months [27,29]. Furthermore, several studies also reported a significant effect with the combination of HA and CS, Porru et al assumed that HA/CS may give better longer-lasting therapeutic effects than the individual compounds [17,23,30]. In the present study, although mean difference of VAS in the pure HA subgroup was higher than that in the subgroup with combination of HA and CS, there was no significant difference between subgroups (P = 0.722).…”
Section: Secondary Outcomesmentioning
confidence: 93%
“…Steinhoff et al found a 45% response rate after initial 3 months with instillation of 40 ml CS 0.2%, and Nickel et al reported that instillation of CS 2% produced a 60% response rate at 6 months [27,29]. Furthermore, several studies also reported a significant effect with the combination of HA and CS, Porru et al assumed that HA/CS may give better longer-lasting therapeutic effects than the individual compounds [17,23,30]. In the present study, although mean difference of VAS in the pure HA subgroup was higher than that in the subgroup with combination of HA and CS, there was no significant difference between subgroups (P = 0.722).…”
Section: Secondary Outcomesmentioning
confidence: 93%
“…Single agent intravesical therapy with CS also provided encouraging results [22,23,24]. To maximize the potential for urothelial restoration, and to elucidate the optimal dose and schedule, HA 1.6% and CS 2.0% were combined for intravesical instillation therapy [25,26] with promising results and recently Cervigni et al [27] reported a sustained improvement in symptoms, still apparent at 3-year follow-up, in patients affected by BPS/IC who had been unresponsive to previous treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Porru et al [21], Cervigni et al [52], and Giberti et al [53] used an intravesical injection of 1.6 % hyaluronic acid and 2.0 % chondroitin sulfate as a treatment for BPS/IC, and observed a decrease of 35-50.76 % in pain, a decrease of 26-57.14 % in voiding frequency, and an increase of 24.90-41 % in voided volume [21; 52]. The study had many limitations; however, they reported an improvement in BPS/ IC symptoms [53].…”
Section: Hyaluronic Acid+chondroitin Sulfatementioning
confidence: 99%